Environmental DNA surveys can determine in-stream dominance of non-native brook charr Salvelinus fontinalis over native brown trout Salmo trutta - Andreas Broman; William F. Englund; Niclas Gyllenstrand; Joacim Näslund (Ecological Indicators)
For effective management of established potentially invasive species it is important to find management target sites (e.g. for depletion or eradication measures). In Sweden, the brook charr is non-native and competes with the native brown trout. Hence, finding methods allowing for rapid screening for potential problem areas is important. Wading electrofishing is the main method used, but eDNA surveys have the potential to replace the former method. Here we evaluate the usage of quantitative single-species eDNA analyses to find sites where brook charr dominates over brown trout. Using the ratio of the estimated relative amount of eDNA for each species, we correctly detect the vast majority of the areas where brook charr is dominating brown trout in the electrofishing results (> 50 % of total abundance or biomass). Surveys using eDNA also have a higher chance to detect brook charr than electrofishing. We also show that quantitative comparisons between eDNA and electrofishing can be interpreted in very different ways depending on handling of outliers and inclusion/exclusion of sites without either catch or eDNA detections of a species in the analyses. Overall, however, even if relationships between catch results and eDNA results are found to be significantly positive under certain assumptions, the ability of eDNA results to predict electrofishing catches at the site level is associated with substantial uncertainties, at the scale of an order of magnitude. No environmental factors were found to clearly affect eDNA concentrations. In conclusion, eDNA is a promising tool to be used for cost-efficient screening of streams where brook charr is a potential ecological problem, but electrofishing still has a strong methodological position for follow-up studies quantifying their actual abundance. The two methods are complementary and one should not completely replace the other.